2016
DOI: 10.4103/0971-9784.191572
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echo diagnosis of perioperative unusual transient left ventricular apical ballooning syndrome

Abstract: Stress cardiomyopathy, or Takotsubo syndrome, is a widely recognized cardiac pathology with a clinical presentation similar to acute coronary syndrome and related to physical or emotional stress. Perioperatively, it is challenging to identify it given the variety of forms and scenarios in which it can present. We describe a 22-year-old patient with an atypical presentation of Takotsubo syndrome during anesthesia induction, which highlights the usefulness of transesophageal echocardiography for the initial diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…37,38 Bruckman et al 39 reported a case that manifested moments after local anesthesia administration and incision in order for materials from previous facial fractures to be removed. Mantilla et al 40 reported TS during the surgical preparation for temporomandibular meniscopexy. In addition, 5 ENT and 4 head and neck cases of TS evolving in the postoperative period were identified (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Bruckman et al 39 reported a case that manifested moments after local anesthesia administration and incision in order for materials from previous facial fractures to be removed. Mantilla et al 40 reported TS during the surgical preparation for temporomandibular meniscopexy. In addition, 5 ENT and 4 head and neck cases of TS evolving in the postoperative period were identified (Table 1).…”
Section: Discussionmentioning
confidence: 99%